Burung yang Baik Dipelihara dan Tidak dalam Serat Ngalamating Kutut - Mirya Anggraini (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This study aims to reveal the meaning of the pekutut bird in Serat Ngalamating Kutut. Material object of this research is Serat Ngalamating Kutut. Serat Ngalamating Kutut consists of nineteen stanzas and contains myths about perkutut bird. The text describes fifteen kinds perkutut bird. Of the fifteen kinds can be divided into two. Nine kinds are good turtles and the other six are bad birds. The results showed, the characteristics of perkutut  birds that have good and bad influence there is in the text. Birds that have good characteristic are recommended to maintain. Contrarily, birds that have bird characteristics that can bring problems are not recommended, even  forbidden to maintain.